Case report of life-threatening complications following cystectomy in a woman with neurogenic lower urinary tract dysfunction treated with indwelling bladder catheter for about 30 years - Maltagliati, Matteo; Sampogna, Gianluca; Secco, Silvia; Galfano, Antonio; Montanari, Emanuele; Micali, Salvatore; Rocco, Bernardo; Spinelli, Michele (Acta Biomedica Atenei Parmensis, 2021)
Patients with neurogenic lower urinary tract dysfunction (NLUTD), specially with indwelling bladder catheter (iBC), have an increased risk of developing bladder stones, incomplete bladder emptying, recurrent urinary tract infections, sepsis, urethral trauma and bladder cancer. We present the case of a patient with a large bladder stone in iatrogenic NLUTD treated with iBC for about 30 years, who underwent a cystectomy followed by several life-threatening complications.